THE RISE OF THE PROFESSION OF ACCOUNTANCY IN ENGLAND. - Murphy, Mary E. (The Accounting Review, 1940)
Abstract The profession of accountancy holds a place of honor in England, ranking with the ministry, medicine and the law. Its traditions have been built up over years of practice and they display a general air of austerity and conservatism. The English accountant should be viewed in relation to the activities of his profession, and in relation to the economic and social aspects of his country. To a marked degree his effectiveness is conditioned by existent legal and financial philosophies. Although the profession of accountancy in England is inextricably bound up with the various Companies Acts it is of interest to note that practicing accountants actually preceded their enactment. English economists and accountants constantly refer in their writings to the separation of ownership from control of company property and the necessity for an accounting to be rendered to the real owners of limited liability companies yet English law appears to be behind social and economic change as it does not, to any important degree, reflect this separation and its implications. The incorporated accountants are generally in favor of English Company Law reform particularly with reference to the profit-and-loss and holding company accounts.